الاقتصاد غير المنظم في سورية الخصائص والأسباب - محمود يوسف; موسى رلا (Latakia University Journal - Economic and Legal Sciences Series, 2015)
يعد الاقتصاد غير المنظم من أبرز القضايا الاقتصادية التي مازالت تأخذ الحيز الواسع من اهتمامات الباحثين، فهو موجود في جميع الدول على اختلاف أنماطها الاقتصادية ويمس جميع الشرائح الاجتماعية وجميع الفئات العمرية كما يشكل هذا النوع من الاقتصاد نسبة عالية من الناتج المحلي الإجمالي لأغلب دول العالم . بناء على ماتقدم جاء هذا البحث لتوضيح مفهوم الاقتصاد غير المنظم ، والتعرف على مكوناته كذلك يوضح البحث أهم الأسباب التي أدت لدفع الأفراد للعمل في الأنشطة غير المنظمة حيث توضح الأثر الكبير للتسرب من المدارس وأثر الفساد الإداري في اتساع حجم الاقتصاد غير المنظم كذلك يوضح أهم خصائص العاملين في الاقتصاد غير المنظم . The informal economy is considered the most important of economic issue which still concerns researchers. It is found in all states with different economic patterns and affects all social strata and all age groups. This type of economy forms a high percentage of the gross domestic product of most countries of the world. Accordingly, this research came to clarify the concept of the informal economy, and identify its components. As well as, this research showed the most important reasons to pay individuals to work at informal activities. Also this research illustrated the significant impact of school dropout and the effect of corruption at increasing the informal economy also showed the most important characteristics of workers in the informal economy.